Criminal Law Policy On Corruption Criminal Acts: Considering The Death Penalty In The Framework Of Restorative Cension - Noerdajasakti, Setiawan; Kristanto, Kiki (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Corruption offenses in Indonesia are positioned as extraordinary crimes that generate systemic impacts on state finances, the national economy, and public trust, thereby necessitating firm and effective criminal law policies. One of the punitive instruments normatively regulated is the death penalty, as specified in Article 2 paragraph (2) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, particularly when corruption is committed under certain circumstances. Nevertheless, in law enforcement practice, this provision has almost never been applied, giving rise to issues concerning its relevance, rationality, and consistency with the objectives of punishment, especially from the perspective of restorative sentencing and human rights protection. This study employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that the death penalty in corruption offenses functions more as a symbolic normative threat than as an applicable sentencing instrument and is less aligned with the orientation toward restoring state financial losses. Therefore, this research emphasizes the need to reform corruption-related criminal law policies by balancing strict law enforcement with the strengthening of restorative sentencing, in order to achieve substantive justice, effective corruption eradication, and the sustainability of the national legal system